FLEXURAL BEHAVIOR OF REINFORCED CONCRETE BEAMS MADE WITH ORDINARY AND HIGH STRENGTH CONCRETES: EFFECT OF INTERFACIAL ROUGHNESS BETWEEN OLD AND NEW CONCRETES - DINKHA, YOUKHANNA ZAYIA; HAIDO, JAMES H.; ALI, MSHEER HASAN (Journal of Duhok University, 2017)
Present endeavor is devoted to investigate the flexural strength of beams fabricated by ordinary concrete (OC) and retrofitted with high strength concrete (HSC). Old part of beams is represented the deteriorated concrete; while the new part is referred to retrofitted portion of the deteriorated beam. Bond strength between two concrete parts of beam was enhanced via preparing rough interfacial surface in various ways, namely, sand blast, holes, grooves and steel brush. Experimental measurements are given in terms of flexural load – deflection relationship and cracking pattern of the beams. It is demonstrated that the beams with sand blast interfacial surface show reasonable performance with high flexural toughness and safer cracking at collapse.